ISOLASI DAN KARAKTERISASI MIKROBA TERMOFILIK PENGHASIL XILANASE DARI LUMPUR PANAS LAPINDO SEBAGAI ALTERNATIF PENGGANTI KLORIN PADA INDUSTRI KERTAS - Habibie, Fadeli Muhammad; Sigres, Divan Probo; Islami S, Luqvia Noer (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This study aimed to isolate xylanase producing microbe from hot mud in Lapindo area disaster. This microbes were supposed to be extremophillic bacterium because of extreme condition of hot mud. This study comrised of sampling hot mud disaster, isolation and characterization of thermophillic isolates, and characterization of thermophillic xylanase. The result showed that 14 xylanolitic isolates were obtained and one isolate (C211) had the best xylanase activity. This enzyme had optimum activity at 50°C and pH 7.0, and showed the hydrolytic activity of 2.60 unit/mL/min. Keyword: xylanase, thermophillic microbe, hot mud disaster, Lapindo